The Relationship between Organization and the Success of the Health Information System at the Health Center in the Kolaka District, Southeast Sulawesi Province - Fajar Kurniawan; Romawati Ibrahim; Ira Nurmala; Marheni Fadillah Harun (PT FORMOSA CENDEKIA GLOBAL, 2022)
Presidential Regulation No. 46 of 2014 found that the program planning that has been carried out so far has not been in accordance with procedures due to inappropriate human resources: organizing: Cooperation and Coordination; data source strengthening: management of data utilization and resource development, operation of Health Electronic Systems; development of Health Information System; weak monitoring and evaluation; and there is no coaching and supervision. The aim of the research is to find out how successful the Health Information System is in organizing the Health Information System in the Health Center in the Kokan Regency. This type of research is quantitative using a cross-sectional study design. This research was carried out from January to February 2022. This research was carried out at the Kolaka District Health Center. The population is all officers who are considered to have a role and responsibility for health services in the Kolaka district. with a total of 579 health workers in the Kolaka district on duty at the puskesmas, with a sample of 90 respondents using the Simple Random Sampling technique